The invention of the passport: surveillance, citizenship and the state - Torpey, John C. (Cambridge studies in law and society, 2018)
"In an obscure paragraph of a package of immigration reforms adopted in 1996, the United States government committed itself to developing "an automated system to track the entry and exit of all non-citizens, thus providing a way of identifying immigrants who stay longer than their visas allow." At the time that the legislation was supposed to be put into effect, however, some in the government came to regard this measure as likely to cause undue complications for millions of border- crossers, and the implementation of the law was postponed for two and a half years"--